Dekoracje maswerkowe szczytu prezbiterium kościoła pw. Wniebowzięcia Najświętszej Marii Panny w Toruniu - Kurkowski, Michał; Pilecka, Elżbieta; Poksińska, Maria (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2014)
Tracery decorations at the top of presbytery in the Church of Th Assumption of the Blessed Virgin Mary in Toruń This article was written as a contribution to studies on medieval architectural detail over the gothic steeples and their decoration with tracery subjects. The top above presbytery of post – Franciscan Saint Mary’s Church in Toruń was the beginning of our research. Working together, we had to analyse the mass, steeples and tracery decorations of this shrine and we treated them together as a coherent whole. Firstly, we limited to the typological and formal analysis within the territorial researches of Ziemia Chełmińska region. Then we indicated some signifiant features which are to be testament to the architect author’s project of this church. Also, we undertook some efforts of full reconstruction as to the original look of the steeple, based on the conservation specifiation by George Cuny from 1899 and a contemporary photographic records by Andrzej Skowroński. Leading our own regional studies on the engraved tracery decorations on the elevations of gothic buildings we successfully reconstructed all the themes and compositions of tracery decorations in the engravings, ornamental borders, panels and blind windows of the top in the presbytery of the mentioned above shrine and to indicate analogies among them. This publication is particularly a valuable result in case of undertaking reconstruction as to original look of church and its art of painting.